Targeting RNA Modifications for Drug Development: The Role of Epitranscriptomics in Pharmacology - Nafiu Sani Barau; Tsutsu Terva Collins; Aliyu Muqaddas Abdulkadir (African Journal of Biochemistry and Molecular Biology Research, 2026)
Epitranscriptomics has emerged as an additional regulatory layer of gene expression mediated by chemical modifications on RNA molecules, with important implications for cellular function and disease. This review synthesizes recent advances in epitranscriptomic research, focusing on major RNA modifications, including N⁶-methyladenosine, pseudouridine, and 5-methylcytosine, and their mechanistic roles in regulating RNA stability, splicing, localization, and translational efficiency through the coordinated actions of writers, erasers, and readers. It further examines the dynamic regulation of RNA modifications under pathological stress conditions and highlights their contribution to disease pathogenesis, particularly in cancer, metabolic disorders, and neurological diseases. In addition, the review discusses emerging pharmacological strategies targeting epitranscriptomic regulators, including small-molecule inhibitors and RNA-based therapeutic approaches. The evidence collectively indicates that RNA modifications represent promising therapeutic targets, while also underscoring persistent challenges related to target specificity, delivery efficiency, and off-target effects. The review concludes that epitranscriptomics constitutes a rapidly evolving frontier in drug discovery and precision pharmacology by expanding current understanding of disease mechanisms and offering new directions for therapeutic innovation.